2017
DOI: 10.1016/j.jsxm.2017.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Heightened Pelvic Floor Muscle Tone and Altered Contractility in Women with Provoked Vestibulodynia

Abstract: Background Pelvic floor muscle (PFM) dysfunctions are reported to be involved in provoked vestibulodynia (PVD). Although heightened PFM tone has been suggested, the relative contribution of active and passive components of tone remains misunderstood. Likewise, alterations in PFM contractility have been scarcely studied. Aims To compare PFM tone, including the relative contribution of its active and passive components, and mus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
69
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(71 citation statements)
references
References 28 publications
1
69
0
1
Order By: Relevance
“…Women may keep their PFMs more relaxed when they are less anxious about a dynamometric protocol. Indeed, Morin et al recorded higher baseline forces at rest and higher stiffness in women with provoked vestibulodynia (PVD) compared to women without vulvar pain, noting that the women with PVD tended to demonstrate more PFM EMG activation during a passive stretch induced by a dynamometer despite attempts to keep their PFMs relaxed. Further, Gentilcore‐Saulnier et al observed that women with PVD had lower PFM tone after a physical therapy program, and the authors suggested that the decrease in tone could be attributed to a decrease in fear or anxiety when stretching was applied to the vaginal tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Women may keep their PFMs more relaxed when they are less anxious about a dynamometric protocol. Indeed, Morin et al recorded higher baseline forces at rest and higher stiffness in women with provoked vestibulodynia (PVD) compared to women without vulvar pain, noting that the women with PVD tended to demonstrate more PFM EMG activation during a passive stretch induced by a dynamometer despite attempts to keep their PFMs relaxed. Further, Gentilcore‐Saulnier et al observed that women with PVD had lower PFM tone after a physical therapy program, and the authors suggested that the decrease in tone could be attributed to a decrease in fear or anxiety when stretching was applied to the vaginal tissues.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the responsiveness, reliability and validity of vaginal palpation have been questioned and may be one explanation for the different findings [22]. In a recent published study, Morin et al compared 56 women with and 56 without PVD using dynamometer and sEMG, and found greater PFM resting forces and stiffness measured with a dynamometric speculum in the group with PVD [9]. In a former reported 4D ultrasound study they also found that women with PVD had a significantly smaller levator hiatus area, a smaller anorectal angle and a larger levator angle plate at rest compared with controls, suggesting that this may have been caused by an increased PFM tone [23].…”
Section: Surface Emgmentioning
confidence: 99%
“…In addition, "vaginal overactivity", lack of pelvic floor muscle strength and "restriction of the vaginal opening" have been hypothesized to be associated with Provoked vestibulodynia (PVD) [3;4]. To date there are few studies assessing these variables in women with PVD compared to controls and the reported findings on hypertonicity of the PFM are contradictory [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The role of brain neuroimaging in CPP patients will be better elucidated in the next section (see Section 3 ). Another recent investigation further assessed neurophysiological modifications in a cohort of Provoked Vestibulodynia [ 126 ], as Pelvic Floor Muscle abnormalities were detected and matched with a surface Electromyographic evaluation. Pelvic Floor Muscles of the patients were stiff and more prone to increased resting and activated muscle tone (during stretching) than control subjects; all these abnormalities were documented by surface Electromyographic recording of anomalies.…”
Section: Cpp/cpps Assessment and Objectivation Toolsmentioning
confidence: 99%